First Detection of Borrelia burgdorferi sensu lato DNA in Serum of the Wild Boar (Sus scrofa) in Northern Portugal by Nested- PCR - Faria, Ana Sofia (2017)
Lyme borreliosis is the most common tick-borne zoonosis in the northern hemisphere. Several vertebrates are crucial in the epidemiological cycle of Borrelia burgdorferi sensu lato, but the role of wild boar as a reservoir is still unknown. Sera were collected from 90 wild boars shot in the Trás-os-Montes region, Northern Portugal (hunting season 2011/2012). In this study, Borrelia DNA was detected for the first time by nested-PCR in three different sera, suggesting that the wild boar may be a potential reservoir for this spirochete. Sequencing results show 100% similarity with Borrelia afzelii. Further studies are needed to evaluate the public health risks associated with boar hunting.